Improvisation and social aesthetics - Born, Georgina; Lewis, Eric 1961-; Straw, Will 1954- (Duke University Press, 2017)
After relational aesthetics : improvised music, the social, and (re)theorizing the aesthetic / Georgina Born -- Scripting social interaction : improvisation, performance, and Western "art" music / Nicholas Cook -- From the American civil rights movement to Mali : reflections on social aesthetics and improvisation / Ingrid Monson -- From network bands to ubiquitous computing : Rich Gold and the social aesthetics of interactivity / George E. Lewis -- The social aesthetics of swing in the 1940s : or the distribution of the non-sensible / David Brackett -- What is "great Black music"? The social aesthetics of the AACM in Paris / Eric Lewis -- Kenneth Goldsmith and uncreative improvisation / Darren Wershler -- Strayhorn's queer arrangements / Lisa Barg -- What's love got to do with it? Creating art, creating community, creating a better world / Tracey Nicholls -- Improvisation in New Wave cinema : beneath the myth, the social / Marion Froger, translated by William Straw -- Social aesthetics and transcultural improvisation : Wayde Compton and the performance of Black time / Winfried Siemerling -- Devices of existence : contact improvisation, mobile performances, and dancing through Twitter / Susan Kozel -- The dramaturgy of spontaneity : improvising the social in theater / Zoë Svendsen
Includes bibliographical references and index. - Description based on print version record
Keywords: Geschichte; Improvisation (Music) / Social aspects; Music / Social aspects; Aesthetics / Social aspects; Arts and society; Soziale Funktion; Improvisation; Kunstsoziologie; Interaktion; Kunst; Gesellschaft; Musik; Aufsatzsammlung